Effect of Facial Chuna Manual Therapy Combined with Korean Medicine Treatmeant for Bell's Palsy - Yeon Ah Choi; Soo Min Ryu; Seung Min Lee; You Jin Heo; Eun young Lee; Cham Kyul Lee; Na Young Jo; Jeong-Du Roh (MEDrang Inc., 2022)
The effect of combined Korean medicine treatment including facial chuna manual therapy was retrospectively investigated in patients with Bell's palsy. There were 16 patients (14 males) who received 2 months outpatient treatment following > 14 days of hospitalization. The Yanagihara score and House-Brackmann grade were used to measure the severity of symptoms and recovery. The patients (mean age 58.5 ± 24.74 years) were categorized based on their medical history of hypertension (n = 10), diabetes millitus (n = 10), or oral intake of steroids early in the diagnosis of Bell's palsy (n = 10). There was no difference between patients who had or did not have a previous history of diabetes mellitus or oral steroid. Both the Yanagihara-score and House-Brackmann grade improved significantly in the total patient sample after treatment (p < 0.001). Combined Korean medicine including facial chuna manual therapy may have a beneficial effect on patient symptoms and recovery.